Surgical Procedures and Team Compliance with the Surgical Safety Checklist - Budi Prasetyo, Agus; Negoro, Widigdo Rekso; Rodli, Muhammad; Sintara, Sindu; Permana, Annes Rindy (Jurnal Keperawatan Profesional (KEPO), 2025)
Patient safety is a critical component of surgical procedures, with the Surgical Safety Checklist (SSC) playing a key role in minimizing medical errors. However, its implementation in healthcare settings continues to face challenges in medical team compliance. This study aimed to examine the relationship between the type of surgical procedure and the level of compliance of medical teams in implementing SSC. An analytic survey with a cross-sectional approach was conducted at a maternal and child specialty hospital in urban Yogyakarta. Data were collected through observation of 65 surgical procedures using a checklist based on the three SSC phases (sign-in, time-out, sign-out), and analyzed using the chi-square test. Results showed elective surgeries were more dominant (55,4%), with the majority of patients undergoing cesarean section (84,6%). A significant association was found between surgery type and compliance during the time-out (p-value = 0,004) and sign-out (p-value = 0,011) phases, but not during the sign-in phase (p-value = 0,195). Overall, only 27,7% of surgeries were performed with full SSC compliance. These findings indicate that surgical procedure type significantly influences SSC compliance, particularly in the time-out and sign-out phases, and underline the need for targeted system strengthening through structured training, standardized workflow integration, and continuous compliance monitoring to improve patient safety outcomes.